SPE Annual Technical Conference and Exhibition 2007
DOI: 10.2118/110470-ms
|View full text |Cite
|
Sign up to set email alerts
|

Field Validation of Drillpipe Rotation Effects on Equivalent Circulating Density

Abstract: It is important to predict the Equivalent Circulating Density (ECD) of fluids as closely as possible for safe drilling and completion of wells. This is especially true for those challenging wells where the margin between hole collapse and formation fracturing is very narrow. These characteristics of narrow safe drilling windows are commonly seen in extended-reach drilling (ERD) and deepwater wells, and pose significant drilling and cementing challenges. Over recent years, the changes in ECD c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…The increase was less pronounced when the rotation rate continued to increase further up to 120rpm. Fiveteen years later Hemphill et al [27] reported similar results for a North Sea well. Field data also showing a reduction in annular frictional pressure losses with increased drill string rotation does also exist [31] showing the complexity of the flow problem.…”
Section: Field Evaluationsmentioning
confidence: 73%
See 1 more Smart Citation
“…The increase was less pronounced when the rotation rate continued to increase further up to 120rpm. Fiveteen years later Hemphill et al [27] reported similar results for a North Sea well. Field data also showing a reduction in annular frictional pressure losses with increased drill string rotation does also exist [31] showing the complexity of the flow problem.…”
Section: Field Evaluationsmentioning
confidence: 73%
“…Unlike the results from the majority of the laboratory studies, most of the field measurements [22][23][24][25][26][27][28][29][30] have shown a significant increase in pressure loss as the pipe rota tion increases. The discrepancy between lab observations and field measurements can be attributed to several factors, such as operat ing with multiple dimension scales, drillpipe wobbling or instabil ity, the irregular geometry of the wellbore, tool joint effect, far too simple fluid systems in the laboratory or a combination of these factors.…”
Section: Field Evaluationsmentioning
confidence: 95%
“…ANNs are at the leading edge of computational systems used to produce, or at least mimic, intelligent behavior. ANN is capable of resolving paradigms that linear computing cannot process (Andagoya et al 2015;Hemphill et al 2007;Omosebiet al 2012).…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…Unlike classical AI techniques which directly emulate rational and logical reasoning, neural networks are able to reproduce the underlying processing mechanisms which give rise to intelligence as an emergent property of complex adaptive systems (Shanmuganathan and Samarasinghe 2016). ANN systems have successfully been developed and deployed to solve capacity planning, pattern recognition, intuitive problem-related aspects, robotics, and business intelligence (Andagoya et al 2015;Hemphill et al 2007).…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
See 1 more Smart Citation